2022
DOI: 10.3389/fimmu.2022.1067721
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy and safety of belimumab for the treatment of refractory childhood-onset systemic lupus erythematosus: A single-center, real-world, retrospective study

Abstract: ObjectiveThis study aimed to investigate the efficacy and safety of belimumab for treating children with refractory childhood-onset systemic lupus erythematosus (cSLE).MethodsTwenty-six cSLE patients who received belimumab treatment in our hospital from January 2020 to September 2021 (23 of them for more than 52 weeks) were enrolled in this study. Their clinical and laboratory data, assessment of disease activity, glucocorticoid dosage, and treatment-emergent adverse events (TEAEs) were retrieved for analysis.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
1
0
5

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 33 publications
0
1
0
5
Order By: Relevance
“…Препарат разрешен для лечения детей с СКВ в 2019 г. на основании результатов международного рандомизированного плацебо-контролируемого исследования PLUTO (The Pediatric Lupus Trial of Belimumab Plus Background Standard Therapy) [11]. Показана высокая эффективность препарата в отношении купирования слизисто-кожных проявлений СКВ, суставного синдрома, тромбоцитопении, а также при необходимости быстрого снижения дозы пероральных глюкокортикоидов [11,14], что было актуальным и для нашей пациентки. По данным J.S.…”
Section: Discussionunclassified
See 2 more Smart Citations
“…Препарат разрешен для лечения детей с СКВ в 2019 г. на основании результатов международного рандомизированного плацебо-контролируемого исследования PLUTO (The Pediatric Lupus Trial of Belimumab Plus Background Standard Therapy) [11]. Показана высокая эффективность препарата в отношении купирования слизисто-кожных проявлений СКВ, суставного синдрома, тромбоцитопении, а также при необходимости быстрого снижения дозы пероральных глюкокортикоидов [11,14], что было актуальным и для нашей пациентки. По данным J.S.…”
Section: Discussionunclassified
“…Белимумаб хорошо переносится, инфузионные и серьезные постинфузионные реакции гиперчувствительности не зафиксированы [11,14]. Частота нежелательных реакций в исследовании PLUTO в группе белимумаба была сопоставима с таковой в группе плацебо (79,2 и 82,5% соответственно) [11]; большинство нежелательных реакций были легкими и средней тяжести [11].…”
Section: Discussionunclassified
See 1 more Smart Citation
“…A retrospective, single-center study revealed that belimumab administration in pediatric patients with childhood-onset SLE has demonstrated positive effects on laboratory parameters, disease activity reduction, and a potential decrease in glucocorticoid dosage requirements. Furthermore, belimumab has exhibited a favorable safety record ( 54 ). Povetacicept, an enhanced dual APRIL/BAFF antagonist, demonstrates remarkable improvements in multiple disease indicators in a murine lupus model ( 55 ).…”
Section: Systemic Lupus Erythematosusmentioning
confidence: 99%
“…B. für den ZNS-Lupus und -wie erwähnt -die LN nicht zugelassen. Es gibt inzwischen einige Fallserien für den Einsatz von Belimumab auch beim refraktären Lupus [4]. In einer chinesischen Studie wurden 26 Patienten mit refraktärem Lupus über einen Zeitraum von 6-20 Monate mit Belimumab therapiert.…”
Section: Belimumabunclassified